Parallel texts from the Swedish Work Environment Authority - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts downloaded from the websites of the Swedish Work Environment Authority. The txt files that are available are the result of running the pdf files through the pdftotext command from an ubuntu shell.

Parallella texter nedladdade från Arbetsmiljöverkets webbplats. De txt-filer som finns tillgängliga är resultat ur en körning av kommandot pdftotext i ubuntu-skal.
Parallella texter från Arbetsmiljöverket
Keywords: Safety Management; Säkerhetshantering; work environment; arbetsmiljö; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur